Meridional Ocean Carbon Transport - Aldama-Campino, Aitor; Fransner, Filippa; Ödalen, Malin; Groeskamp, Sjoerd; Yool, Andrew; Döös, Kristofer; Nycander, Jonas (Global Biogeochemical Cycles, 2020)
The ocean's ability to take up and store CO2 is a key factor for understanding past and future climate variability. However, qualitative and quantitative understanding of surface-to-interior pathways, and how the ocean circulation affects the CO2 uptake, is limited. Consequently, how changes in ocean circulation may influence carbon uptake and storage and therefore the future climate remains ambiguous. Here we quantify the roles played by ocean circulation and various water masses in the meridional redistribution of carbon. We do so by calculating streamfunctions defined in dissolved inorganic carbon (DIC) and latitude coordinates, using output from a coupled biogeochemical-physical model. By further separating DIC into components originating from the solubility pump and a residual including the biological pump, air-sea disequilibrium, and anthropogenic CO2, we are able to distinguish the dominant pathways of how carbon enters particular water masses. With this new tool, we show that the largest meridional carbon transport occurs in a pole-to-equator transport in the subtropical gyres in the upper ocean. We are able to show that this pole-to-equator DIC transport and the Atlantic meridional overturning circulation (AMOC)-related DIC transport are mainly driven by the solubility pump. By contrast, the DIC transport associated with deep circulation, including that in Antarctic bottom water and Pacific deep water, is mostly driven by the biological pump. As these two pumps, as well as ocean circulation, are widely expected to be impacted by anthropogenic changes, these findings have implications for the future role of the ocean as a climate-buffering carbon reservoir.
Keywords: Sørishavet; biogeokjemi; bunnvann; karbon syklus; karbondioksid; klimatologi; oseanografi; vannmasser

Controls of the global overturning circulation of the ocean - Roquet, Fabien; Bell, Michael J.; de Boer, Agatha M.; Ferreira, David; Jones, C. Spencer; LaCasce, Joseph H.; de Lavergne, Casimir; Marshall, David P.; Munday, David R.; Nycander, Jonas; Ödalen, Malin (npj Climate and Atmospheric Science, 2025)
The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.
Keywords: Sørishavet; geologi; klimaendringer; klimamodeller; oseanografi; paleogeografi; paleoklimatologi; paleoseanografi

Controls of the global overturning circulation of the ocean - Roquet, Fabien; Bell, Michael J.; de Boer, Agatha M.; Ferreira, David; Jones, C. Spencer; LaCasce, Joseph H.; de Lavergne, Casimir; Marshall, David P.; Munday, David R.; Nycander, Jonas; Ödalen, Malin (npj Climate and Atmospheric Science, 2025)
The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.
Keywords: Sørishavet; global klimamodell; klimamodeller; klimatologi; meteorologi; oseanografi; paleoseanografi